Generalist practitioners’ self-rating and competence in electrocardiogram interpretation in South Africa - Langalibalele H. Mabuza; Pindile S. Mntla (African Journal of Primary Health Care & Family Medicine, 2020)
Background: Electrocardiogram (ECG) is the only practical, non-invasive method of recording and analysing cardiac abnormalities. It enables a primary healthcare (PHC) clinician to detect cardiac and non-cardiac abnormalities, some potentially life-threatening. Their early detection could save a patient’s life. Aim: The aim of this study was to evaluate the competence of generalist practitioners in ECG interpretation. Setting: This study was conducted at the Annual Refresher Course, Council for Scientific and Industrial Research (CSIR), Pretoria. Methods: A cross-sectional study was conducted amongst 93 generalist practitioners, using a self-administered questionnaire containing 20 ECG tracings, commonly encountered in PHC. The tracings were categorised into primary ECG parameters, ECG emergencies and common ECG abnormalities. Competence was determined by the generalist practitioner’s number of correctly interpreted ECG tracings. Data associations were computed using the Fisher’s exact test. Statistical significance was set at p ≤ 0.05. Results: Correct heart rate calculation was achieved by 14/83 (16.9%), ECG rhythm by 7/83 (8.4%), acute antero-septal myocardial infarction (MI) by 29/83 (34.9%), atrial fibrillation by 19/83 (22.9%) and cute inferior MI by 22/83 (26.5%) generalist practitioners. No correlation was found between the practitioners’ number of years in practice and competence in ECG interpretation (p 0.05). The total number of correct answers achieved by all practitioners was 274/1860 (14.7%). Conclusion: The generalist practitioners had poor competency on ECG interpretation regardless of the number of years in practice. Their poor self-rating corresponded with the number of correct answers they provided. There is a need for continuous education in ECG interpretation.